2018
DOI: 10.1021/acsnano.7b07874
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Specific in Vivo Gene Editing Using Cationic Lipid-Assisted Polymeric Nanoparticles

Abstract: The CRISPR/Cas9 gene editing technology holds promise for the treatment of multiple diseases. However, the inability to perform specific gene editing in targeted tissues and cells, which may cause off-target effects, is one of the critical bottlenecks for therapeutic application of CRISPR/Cas9. Herein, macrophage-specific promoter-driven Cas9 expression plasmids (pM458 and pM330) were constructed and encapsulated in cationic lipid-assisted PEG-b-PLGA nanoparticles (CLAN). The obtained nanoparticles encapsulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
138
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(144 citation statements)
references
References 34 publications
(46 reference statements)
0
138
0
Order By: Relevance
“…In this study, cationic lipid‐assisted PEG‐ b ‐PLGA nanoparticles (CLAN) were used to pack the plasmids, pM330 or pM458, that contain the human CD68 promoter to drive gene expression in specific cells (monocytes and macrophages). The mice were treated by intravenous injection of CLANs to disrupt the expression of netrin‐1 genes in monocytes and macrophages specifically, and the results obtained suggested that this could reduce macrophage retention and ameliorate the profiles of glucose tolerance and insulin sensitivity to control T2D (Figure D) …”
Section: Non‐viral Vectors Of Crispr‐cas9mentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, cationic lipid‐assisted PEG‐ b ‐PLGA nanoparticles (CLAN) were used to pack the plasmids, pM330 or pM458, that contain the human CD68 promoter to drive gene expression in specific cells (monocytes and macrophages). The mice were treated by intravenous injection of CLANs to disrupt the expression of netrin‐1 genes in monocytes and macrophages specifically, and the results obtained suggested that this could reduce macrophage retention and ameliorate the profiles of glucose tolerance and insulin sensitivity to control T2D (Figure D) …”
Section: Non‐viral Vectors Of Crispr‐cas9mentioning
confidence: 99%
“…(D) Macrophage‐specific in vivo gene editing using cationic lipid‐assisted polymeric nanoparticles. Reproduced with permission…”
Section: Non‐viral Vectors Of Crispr‐cas9mentioning
confidence: 99%
See 1 more Smart Citation
“…With the guidance of the sgRNA-targeting Ntn1 gene, the CLANs specifically edit the Ntn1 gene only in macrophages andr educe the expression of netrin1a nd improve typeIIdiabetes symptomsinv ivo (Figure3C). [35] Al arge number of polymer-based nanoparticles are useful for the deliveryo fg ene-editingt oolboxes.P olyethyleneimine (PEI) is ap opular polymer for CRISPR/Cas9d elivery.F or instance, ag raphene oxide-polyethyleneg lycol-polyethyleneimine nanocarrier can load Cas9/gRNAt hrough physical absorptionand p-stacking interactions. This method achievesefficient gene editing in AGS cells.…”
Section: Physical Deliverymentioning
confidence: 99%
“…) A recent study by Finn et al used biodegradable lipid nanoparticles complexed with Cas9-mRNA and sgRNA to knock-out the mouse Transthyretin (TTR) gene in the liver, the murine homolog of a therapeutic target for amyloidosis in humans 50). …”
mentioning
confidence: 99%